Developing indicators for evaluating the integration of Islamic values in the academic curriculum at International Islamic University Malaysia: a preliminary findings - Mamat, Arifin; Ismail, Nik Ahmad Hisham; Hussien, Suhailah; Che Haron, Sueraya; Ssekamanya, Siraje Abdallah (2012)
The main purpose of this study is to firstly identify the constructs and dimensions that represent the works of integration of Islamic values in the curriculum as had been practiced by the different Kulliyyahs of IIUM and secondly to develop indicators for evaluating such integration by utilizing Balanced Scorecard Framework. The study consists of two phases; the first phase involved focus group discussion and the second involved a survey. Data gathered in the first phase were analysed using thematic approach; categorization of themes. The second phase involved analysis of survey data using descriptive approach. Findings of the study showed that Islamization of Knowledge (IOK) is the important mission of IIUM, the process of Islamization for teaching and learning among academics at IIUM are good, the participants perceived that they have integrated IOK in the contents and practices of their subject matters, IOK is evident during class presentation and assignments. Majority of the participants referred to their respective colleagues for IOK and the outcomes and product of IOK could be traced from student’s assignment and student’s project. Finally the participants revealed that IOK can also be observed through positive improvement in attitude and appearance among IIUM students. The study suggested few recommendations for enhancement and improvement of IOK such as developing the IOK indicators to reflect the needs for postgraduate and undergraduate programmes, aggressively and constantly promoting IOK among staff of IIUM, including IOK trainings as part of staff development programme at the IIUM, crystalizing the process and procedures of IOK to academic staff, enhancing the process and procedures to evaluate IOK among IIUM academic staff and encouraging works on IOK.